Pengembangan Sistem Informasi Pengarsipan Dokumen di Kantor Urusan Sosial Timor Tengah Utara Menggunakan Pengembangan Perangkat Lunak Adaptif (ASD) - Yoseph Pius Kurniawan Kelen; Antonius Mario Sanbein (Departement Information Systems Universitas Kebangsaan Republik Indonesia, 2026)
Document archiving plays an important role in supporting administrative services within government institutions. At the Social Affairs Office of North Central Timor Regency, archiving activities are still carried out manually by recording incoming and outgoing correspondence in logbooks. This process often causes difficulties in document retrieval, report preparation, and archive management, especially when records increase or logbooks are lost or damaged. Therefore, this study aims to develop a web-based document archiving information system using the Adaptive Software Development (ASD) approach. The system was designed using Use Case Diagrams and Activity Diagrams and implemented using PHP and MariaDB. System testing was conducted using the Black-Box Testing method to evaluate system functionality. The results show that all system functions operated according to the specified requirements. The developed system improves the efficiency of archive management, facilitates document retrieval, and reduces the risk of data loss compared to the previous manual process. In addition, this study demonstrates the applicability of the ASD approach in developing document archiving systems for local government institutions.